Carbon dioxide solar assisted heat pump system for space cooling and heating - Baradey, Yehya A.A (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Solar assisted heat pump (SAHP) system is a conventional heat pump system where solar energy is the main or supplementary heat source. In the normal installation, heat rejection occurs directly to the ambient air as waste heat. In tropical countries such as Malaysia, air conditioners are running almost in every building, so that the amount of waste heat from the heat pump systems is huge. It is more prudent to exploit this heat for other applications such as water heating, drying, and desalination instead of throwing it away. Meanwhile, SAHP systems usually operate by HCFC synthetic refrigerants such as R134a. Synthetic refrigerants cause Global Warming and Ozone Depletion. Replacing the synthetic refrigerants by CO2 in heat pump systems will be more environmentally friendly. In current contribution, carbon dioxide was used as refrigerant to improve the performance of the system and to make it environmentally friendly. Waste heat from the gas cooler was utilized to provide hot water for domestic applications as well as to operate the desalination unit. Dryer was placed as secondary gas cooler to provide additional cooling for the refrigerant which increases the COP of the system. Solar energy was integrated in the system as supplementary heat source to decrease the work done by the compressor and therefore improve the performance of the system. The modified system was designed, built and experimentally tested to study its performance, and to investigate the feasibility of the system. The system consisted of R744 trans-critical compressor, air finned-tube room evaporator, evaporator collector to provide heat to the refrigerant, internal heat exchanger, Air Gap Membrane Desalination Unit (AGMD), air convective dryer, water tank, water flat plate solar collector, and two gas coolers. The experimental part was carried out on the R744 test rig at NTNU. The AGMD unit and the water flat plate collector were experimentally tested on the rooftop in IIUM. Simulation for the system components was conducted using the commercial release of ANSYS FLUENT FLOW 14.5 and MATLAB software. Results showed that the system was able to provide hot water with temperature of 56°C. oC for domestic applications. Water solar collector, which was used to provide hot water during the day, provided hot water at same temperature as well. Effect of inlet temperature of coolant in the first gas cooler was studied and it was concluded that the higher inlet temperature the lower COP. Impact of ambient temperature on the performance of the air convective dryer was theoretically studied. Theoretical results showed that the higher ambient temperature the higher outlet temperature of the refrigerant (R744) from the dryer, which negatively influences its performance. Effect of ambient temperature on the coefficient of performance of the system was also carried out. It was concluded that increasing the ambient temperature has negative impact on both heating and cooling COP of the system. Heating and cooling COPs of the system were recorded as 4.1 and 3.4 respectively. Production rates of fresh water from the AGMD unit under different inlet temperatures of seawater were experimentally examined. Results showed that maximum amount of produced fresh water obtained was 45.3 Ml/hr at inlet temperature of feed water of about 55°C..